Influence of disc-fovea angle and retinal blood vessels on interindividual variability of circumpapillary retinal nerve fibre layer. Issue 4 (12th August 2015) - Resch, Hemma; Pereira, Ivania; Hienert, Julius; Weber, Stephanie; Holzer, Stephan; Kiss, Barbara; Fischer, Georg; Vass, Clemens
Abstract : Background: To assess whether intersubject variability of circumpapillary retinal nerve fibre layer (RNFL) thickness in healthy subjects acquired with spectral domain optical coherence tomography (SD-OCT) can be reduced by considering the disc-fovea angle (DFA), either alone or together with a compensation based on retinal blood vessel distribution (RVD). Methods: 106 healthy volunteers underwent SD-OCT examination centred on the optic disc (OD) and on the macula. OD contours and foveal positions were automatically calculated. RVD at 3.4 mm diameter circle was manually assessed. We made two approaches to reduce interindividual variability in RNFL values using compensation processes; RVD compensation: RNFL thickness values were compensated according to RVD variation (RNFLRVD ) and DFA compensation: we shifted the RNFL thickness measurements according to the DFA (RNFLDFA ). Coefficient of variance (CoV) was calculated in 12 clock hour sectors for original RNFL (RNFLo), RNFLDFA, RNFLRVD and RNFL with both compensation methods (RNFLDFA-RVD ). Results: Compared with the mean CoV of RNFLO, mean CoV of RNFLDFA, RNFLRVD and RNFLDFA-RVD was changed by −0.71% (p>0.05), −9.51% (p<0.001) and −7.55% (p=0.001), respectively. When compared with RNFLDFA, RNFL DFA-RVD significantly reduced the mean CoV by −6.69% (p=0.001), while compared with RNFLRVD, RNFL DFA-RVD did not significantly increase the mean CoV (+2.20%), (p>0.05). Conclusions: Although reaching an improvement in some sectors, rotation of RNFL measurements according to the DFA on average does not reduce intersubject variability of RNFL. However, adjusting for RVD reduced the variance significantly. The results reinforce our work in assessing RVD as an important anatomical factor responsible for intersubject variability in RNFL measurements.